Persiapan Diri dalam Dakwah - Syafi’i, Ahmad Adnan Agus (Fakultas Dakwah IAIN Purwokerto, 2017)
Religious proselytizing (summerring or praying) is a noble duty, which to do it a knowledge is a needed, among of the them are studied on religius proselytizing (summering or praying) management and the most important of it is undestanding the preparation or religious proselytizing (summering or praying) planning for a prayyer.Proselytizer should learn by pray close attention on religious guidance and steps of Islamic fighter, the holy Qur’an, the messenger and its doctrine, the attitude of discripies and scholar of Islam. Its very important as capital in religious proselytizing planning. Among of paramount importance in religious proselyting planning is having seriousness, the scope of religious proselytizing planning of seriuousness is try seriously in teaching the soul to always back (entrust) to Allah, by decorating ourself in god self, sacriface the soul, evacuate until leaving the home town and family, and by generosity the wealth.Proselytizer also has to have a motivation that can build them, among the motivation of religious proselytizing is undestanding the peculiarity of religious proselytizing, so it can grow high awareness and spirit of religious proselytizing fighting. Dakwah adalah tugas mulia, maka untuk melaksanakannya memerlukan ilmu pengetahuan, di antaranya yaitu mempelajari manajemen dakwah, dan hal penting dalam mempersiapkan manajemen dakwah adalah planning dakwah bagi da’i.Da’i semestinya mempelajari dengan mencermati petunjuk agama dan langkah-langkah para pejuang Islam; al-Qur’an, Rasulullah dan ajarannya, perilaku para sahabat, dan para ‘ulama Islam. Hal ini sangat penting sebagai modal dalam planning dakwah. Di antara yang terpenting dalam planning dakwah adalah memiliki kesungguh-sungguhan, adapun ruang lingkup planning dakwah dengan kesungguhan adalah; Besungguh-sungguh di dalam mendidik jiwa untuk tetap kembali (berpasrah) kepada Allah, dengan penghiasan diri di dalam ketauladaan, mengorbankan jiwa, berhijrah sampai meninggalkan kampung halaman dan keluarga, dan dengan kedermawanan harta. D’ai juga harus memiliki motivasi yang dapat membangunnya, di antara motivasi dakwah adalah memahami keistimewaan dakwah, sehingga menumbuhkan kesadaran yang tinggi dan menyemangatkan perjuangan dakwah.